Fluorescent Gold Nanoclusters with Interlocked Staples and a Fully Thiolate‐Bound Kernel. Issue 38 (16th August 2016) - Gan, Zibao; Lin, Yuejian; Luo, Lun; Han, Guangmei; Liu, Wei; Liu, Zhengjie; Yao, Chuanhao; Weng, Linhong; Liao, Lingwen; Chen, Jishi; Liu, Xu; Luo, Yi; et al.
Abstract: The structural features that render gold nanoclusters intrinsically fluorescent are currently not well understood. To address this issue, highly fluorescent gold nanoclusters have to be synthesized, and their structures must be determined. We herein report the synthesis of three fluorescent Au24 (SR)20 nanoclusters (R=C2 H4 Ph, CH2 Ph, or CH2 C6 H4 t Bu). According to UV/Vis/NIR, differential pulse voltammetry (DPV), and X‐ray absorption fine structure (XAFS) analysis, these three nanoclusters adopt similar structures that feature a bi‐tetrahedral Au8 kernel protected by four tetrameric Au4 (SR)5 motifs. At least two structural features are responsible for the unusual fluorescence of the Au24 (SR)20 nanoclusters: Two pairs of interlocked Au4 (SR)5 staples reduce the vibration loss, and the interactions between the kernel and the thiolate motifs enhance electron transfer from the ligand to the kernel moiety through the Au−S bonds, thereby enhancing the fluorescence. This work provides some clarification of the structure–fluorescence relationship of such clusters. Abstract : Three thiolate‐protected gold nanoclusters were synthesized to enable structure–fluorescence relationship studies. The clusters consist of a bi‐tetrahedral Au8 kernel protected by four tetrameric Au4 (SR)5 motifs. Their unusual fluorescence is due to two pairs of interlocked Au4 (SR)5 staples and interactions between the kernel and the thiolate motifs.